PERAN DAN FUNGSI SELF-ACCESS LEARNING CENTER DI UNY - Jamilah, Jamilah; Priyana, Joko; Suciati, Suciati (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: Role and Function of Self-Access Learning Center in UNY). This study aims to develop self-access reading materials for learning English independently. This research was conducted with the Research and Development model by following the steps: needs assessment, design and development, evaluation and revision, and a try out field. Data collected through questionnaires. There are three questionnaires used, namely for needs assessment, for expert judgment, and for field trials. Sample for needs assessment was taken by proportional quota sampling representing all faculties at UNY, while samples for the trial were taken purposively. The collected data was analyzed descriptively quantitatively. The results of the study showed that SAC UNY had not been widely known by students. Even after the introduction of online tutorials since 2015, the SAC is no longer visited by students. Thus the teaching materials developed should also be in the form of online. SAC socialization was also deemed necessary so that students were more familiar with the existence, function, and role of SAC in developing the English language skills of UNY students.Keyword: SAC, teaching materials, language skills, English